Comparison between two anticoagulant regimens to prevent thrombosis in atrial fibrillation: an analysis mediated by transesophageal echocardiography. (8th February 2021) - Fusini, L; Maltagliati, AC; Alimento, ML; Italiano, G; Pepi, M; Tamborini, G; Galli, CA
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Atrial fibrillation (AF) is the most common cardiac arrhythmia causing left atrial appendage thrombosis (LAA-T) which can result in cerebral and systemic embolism. Nowadays, both vitamin K antagonists (VKA) and Direct Oral Anti Coagulants (DOAC) are effective for the prevention of ischaemic stroke in AF. Transesophageal echocardiography (TEE) is the best method to detect LAA-T in AF. However, data on the prevalence of LAA-T are lacking. Purpose. The aim of the study was 1) to evaluate the prevalence of LAA-T in patients affected by AF, receiving different anticoagulation regimens and candidates to cardioversion or catheter ablation 2) to correlate the presence of LAA-T with clinical and echocardiographic data. Methods. This is an observational, single-center study including 796 patients (73% male) with AF. TEE before cardioversion or catheter ablation was performed in all patients. Patients with mechanical prosthetic valve and severe mitral stenosis were excluded. Patients were divided in 2 groups according to anticoagulation regimen: Group 1 including patients on DOAC (dabigatran, rivaroxaban, apixaban, edoxaban) and Group 2 including patients on VKA at therapeutic dose. Results: Group 1 included 369 patients (46%), Group 2 427 (54%). Age, CHA2DS2-VASc score, sex and pathology distribution (lone FA, hypertension, valve disease, ischemic cardiomyopathy, dilated cardiomyopathy, hypertrophic cardiomyopathy) were similar in the 2 groups. The overall prevalence of LAA-T was 43 cases (5%). Similar percentage of LAA-T was found regardless of anticoagulation regimen (Group 1: 16 cases, 4%; Group 2: 27 cases, 6%, p = 0.220). No difference in LAA-T prevalence was detected within Group 1 for different DOACs (p = 0.547). Patients with LAA-T were more frequently older (p = 0.023), female (p = 0.001), with higher CHA2DS2-VASc score (p = 0.002), affected by hypertrophic cardiomyopathy (p = 0.019), valve disease or bioprostetic valve (p = 0.001) regardless of anticoagulation regimen. A total of 697 patients (88%) were scheduled for cardioversion or catheter ablation. Cardioversion was successful in 667 patients (95%) without any ischemic event. Only 1 patient (0.1%) undergoing catheter ablation had a major ischemic event. Conclusions: Efficacy of anticoagulation with VKA and DOAC is similar in preventing LAA-T in patients with AF. However, despite optimal adherence to a therapeutic regimen, several clinical factors (age, gender, high CHA2DS2-VASc score, hypertrophic cardiomyopathy and valvular disease) were associated with higher prevalence of LAA-T. TEE guided approach to cardioversion may prevent the risk of embolic events regardless of anticoagulation regimen used.